The Oxford anthology of modern Indian poetry - Dharwadker, Vinay, 1954-; Ramanujan, A. K., 1929-1993. (Delhi : Oxford University Press, 1994)
Chiefly English translation from fourteen Indian languages.
Includes index.
Keywords: Indic poetry -- 20th century -- Translations into English